Optimasi Sistem Informasi Keuangan dengan Mikrokontroler : Menyederhanakan Proses Pengumpulan dan Pengolahan Data - Riki Wirayuda (STIKes Ibnu Sina Ajibarang, 2025)
Financial information systems play a crucial role in managing and processing company financial data. However, manual data collection and processing often require time and are prone to errors. This study aims to optimize financial information systems by utilizing microcontrollers in the automation of data collection and processing. The method used involved the development of a microcontroller-based prototype system to automate real-time financial data monitoring and reporting. The results showed that the use of microcontrollers significantly improved the efficiency and accuracy of financial data processing, while reducing the time needed for reporting. In conclusion, a microcontroller-based system can be an effective solution to enhance the quality and speed of financial data processing in companies.